2000
DOI: 10.1152/ajpheart.2000.279.6.h2908
|View full text |Cite
|
Sign up to set email alerts
|

Renal vasodilatory influence of endogenous carbon monoxide in chronically hypoxic rats

Abstract: Chronic hypoxia (CH) attenuates systemic vasoconstriction to a variety of agonists in conscious rats. Recent evidence suggests that similarly diminished responses to vasoconstrictors in aortic rings from CH rats may be due to increased endothelial heme oxygenase (HO) activity and enhanced production of the vasodilator carbon monoxide (CO). Thus we hypothesized that a hypoxia-induced increase in HO activity is responsible for decreased vasoconstrictor responsiveness observed in conscious CH rats. CH (4 wk at 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
58
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 44 publications
12
58
3
Order By: Relevance
“…Even so, it remains clear that the antinatriuretic/antidiuretic effects of the HO inhibitor can occur independently of changes in RBF and GFR. Furthermore, our results are in agreement with a study showing that the HO inhibitor zinc protoporphyrin had no effect on baseline RBF (23).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Even so, it remains clear that the antinatriuretic/antidiuretic effects of the HO inhibitor can occur independently of changes in RBF and GFR. Furthermore, our results are in agreement with a study showing that the HO inhibitor zinc protoporphyrin had no effect on baseline RBF (23).…”
Section: Discussionsupporting
confidence: 93%
“…However, other investigators found that HO inhibition had no effect on basal renal hemodynamics (23). It has also been reported that HO inhibition by zinc deuteroporphyrin 2,4-bis glycol (ZnDPBG) promotes regional differences in RBF by decreasing medullary blood flow with no significant changes in cortical blood flow (37).…”
mentioning
confidence: 99%
“…18 HOdependent generation of CO and other products is relevant to the regulation of renal function, because pharmacological inhibition of HO isoforms results in renal vasoconstriction and increased reactivity of the renal vasculature to constrictor agonists. 3,5,20 The present study demonstrates for the first time that the status of NO synthesis influences the urinary concentration Figure 2. Effect of SNAP on CO-generating activity of renal homogenates derived from rats treated with L-NAME for 2 days.…”
Section: Discussionmentioning
confidence: 56%
“…3,5,8,20 For example, it is conceivable that upregulation of renal CO production during NOS inhibition brings about attenuation of the renal vasoconstriction known to be associated with diminished production of NO. 4,5 This notion is in keeping with a recent report that the renal vasoconstriction ensuing after administration of the HO inhibitor SnMP is greatly magnified in rats pretreated with L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is normally low and contributes to HO activity only when it is induced as a result of some pathological condition (8). In vivo studies suggest that endogenous HO products can cause renal vasodilatation, diuresis, and natriuresis because metalloporphyrins (which inhibit HOs) increase blood pressure (14) and decrease renal blood flow (25,42), glomerular filtration rate (4), and pressure natriuresis (18).…”
mentioning
confidence: 99%